Evaluation of TNF-α and IFN-γ Levels in Macrophage of Preeclampsia Mice Model Induced by DOCA and L-NAME - Susanti, Winda Karina; Christina, Yuyun Ika; Dwijayanti, Dinia Rizqi; Rahayu, Sri; Rifa'i, Muhaimin; Djati, Muhammad Sasmito (The Journal of Experimental Life Science, 2024)
Preeclampsia is a pregnancy disorder characterized by high blood pressure, proteinuria, and chronic inflammation that potentially leads to multiorgan failure. This study investigated differences in the relative number of pro-inflammatory cytokines (IFN-γ & TNF-α) in preeclamptic mice induced by DOCA and L-NAME. Eighteen pregnant BALB/c mice (n=6): pregnant mice without any treatment (P), pregnant mice treated with Deoxycorticosterone acetate/DOCA (D), and pregnant mice treated with N-ω-L-arginine Methyl Ester/L-NAME (L) and healthy nonpregnant mice as control (NP). DOCA at 12.5 mg.kg-1 BW was injected subcutaneously before mating and 6.5 mg. kg-1 BW after mating every week for 16 days. L-NAME was administered orally at 75 mg.kg-1 BW daily after five days of gestation. Mice were dissected in the second trimester (day 16), and then the spleen was isolated to analyze the relative number of CD11b+IFN-γ+ and CD11b+TNF-α+ using flow cytometry analysis. The results showed that DOCA and L-NAME induction did not significantly induce the production of TNF-α levels in the macrophage of pregnant mice. However, both DOCA and L-NAME significantly induce the production of IFN-γ levels in the macrophage of pregnant mice. Further evaluation of other markers related to preeclampsia should be done to better understand the roles of DOCA and L-NAME in inducing preeclampsia. Keywords: DOCA, L-NAME, mice, preeclampsia, pregnant.